(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Interest in Russia’s working class, its labor behavior, and ethics has quickened in historical and social science in the past few years. One of the main industrial areas of Russia is its Ural Region – the Urals – where one can find the oldest and largest metallurgical plants in the country. That is why the current research deals with the Ural workers’ labor image, that is, their labor ethics and attitude to work in the late ХIХth-early XXth centuries. The general scientific methods of analysis and synthesis, induction and deduction are utilized to fulfil the study’s aims. Having analyzed a wide range of sources, we have come to the following conclusions: the Ural workers’ labor image in the late ХIХth century was a controversial combination of positive, pragmatic motivation for work, on the one hand, and widespread poor-quality and low-productive labor, as well as laziness and careless attitude to work, on the other hand. Since these features of the Ural workers’ labor ethics, in general, are typical of the Russian working class as a whole, they can be considered an inseparable p/art of the Russian national mentality and should be taken into account while working out modern labor development strategies.